Developing Android-Based Interactive Multimedia with Madurese Culture to Enhance Students’ Learning Outcomes in Classroom Action Research - Fikrotul Azizah; Badrud Tamam (Universitas Muhammadiyah Sidoarjo, 2025)
This study aims to improve Grade VII students’ learning outcomes on the topic of the Life Organization System by implementing the culturally responsive “Bebek Songkem” Android-based interactive multimedia. The media was designed to address students’ difficulties in understanding abstract biological concepts while providing contextual learning linked to local Madurese culture. The research employed the Classroom Action Research (CAR) model of Kemmis and McTaggart, consisting of the stages of planning, action, observation, and reflection. The participants were 30 students of Class VII-B at UPTD SMPN 5 Bangkalan. Data were collected through pre-tests and post-tests in each cycle and analyzed using gain score. The results showed a consistent improvement in learning outcomes. In Cycle I, the average score increased from 33.33 to 57.00 with a gain score of 0.355 (moderate). In Cycle II, the mean score increased from 43.33 to 86.00 with a gain score of 0.761 (high). These findings demonstrate that integrating local cultural elements into interactive multimedia can enhance students’ comprehension, engagement, and overall science learning performance.